PELATIHAN PENGGUNAAN BEBERAPA ALAT PERAGA MATEMATIKA DI SD YPK MARTIN LUTHER SENTANI, KABUPATEN JAYAPURA PROVINSI PAPUA - Tiku Tandiangnga; Diana Setyaningsih; Yuniar Matarru (JURNAL PENGABDIAN PAPUA, 2022)
SD YPK Martin Luther Sentani is one of the elementary schools in Sentani Kota Village. Most of the teacher didn't use any tools in teaching mathematics when they explain about the concept of mathematics. The students study mathematics more by direct explanation from the teacher and followed by exercises that only just about calculating. Whereas, children at the elementary school needs to use a concrete medium in the learning process to understand the theory of mathematics, because they still in the early step of how to think concretely and they need a fun learning method. Monotonous learning make students bored and not interested in learning. Moreover, the knowledge and skill of the teachers in designing the tools that lead to the process are still low. By considering this problem that faced by the teachers of SD YPK Martin Luther Sentani, then there is need to make a program that involved the teachers. The purpose of this program is to informed or to introduce some tools to the teachers that are useful to make the students understand the mathematics more easily, and how to implement in the classroom. In the implementation of this program, using three methods, they are by lecture, ask and question, and games method. This program has increased the understanding and the knowledge of the teachers about using props in the classroom in order to increase the understanding of the students about mathematics concept and to stimulate interest and motivation of the students in SD YPK Martin Luther Sentani.Keywords:  elementary school; mathematics learning; tools; teachers; number